2023
DOI: 10.5658/wood.2023.51.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Resistance of Reinforced Light-Frame Wood Shear Walls

Abstract: In light-frame timber construction, the shear wall is one of the most important components that provide resistance to lateral loads such as earthquakes or winds. According to KDS (Korea Design Standard) 42 50 10, shear walls are to be constructed using wood-based structural sheathing, with studs connected by 8d nails spaced 150 mm along the edge and 300 mm in the field. Even though small-scale residential timber building can be designed to exhibit seismic resistance using light-frame timber shear walls in acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…이에 따라 전통목구조의 구조성능 검토를 위해서는 가 장 큰 하중을 차지하는 지붕하중을 정밀하게 산정하는 것이 무 엇보다 중요하다 (Kim et al, 2021). 전통목구조는 골조와 벽체 의 구성에 따라 거동특성이 크게 영향을 받는다 (Lee et al, 2007). et al, 2016), 구조해석 소프트웨어를 이용한 정밀한 3차원 구 조해석 (Kim, 2015;Kim et al, 2022), 그리고 최근에는 내진성 능 평가에 대한 연구도 수행되었다 (Kim, 2019;Lee and Kim, 2022;Park et al, 2020).…”
Section: 연구 목적unclassified
“…이에 따라 전통목구조의 구조성능 검토를 위해서는 가 장 큰 하중을 차지하는 지붕하중을 정밀하게 산정하는 것이 무 엇보다 중요하다 (Kim et al, 2021). 전통목구조는 골조와 벽체 의 구성에 따라 거동특성이 크게 영향을 받는다 (Lee et al, 2007). et al, 2016), 구조해석 소프트웨어를 이용한 정밀한 3차원 구 조해석 (Kim, 2015;Kim et al, 2022), 그리고 최근에는 내진성 능 평가에 대한 연구도 수행되었다 (Kim, 2019;Lee and Kim, 2022;Park et al, 2020).…”
Section: 연구 목적unclassified
“…Bending strength KS F 2208 Cha et al, 2022;Darwis et al, 2023;Fujimoto et al, 2021;Hadi et al, 2019Hadi et al, , 2022Iswanto et al, 2017;Kang et al, 2023;Kim et al, 2020;Lee and Jang, 2023;Lee and Oh, 2023;Liu et al, 2022;Maulana et al, 2017;Oh, 2021Oh, , 2022Özcan and Korkmaz, 2019;Park et al, 2015bPark et al, , 2016Qi et al, 2019;Savero et al, 2020;Schulz et al, 2021;Song and Kim, 2023;Sumardi et al, 2022;Trisatya et Huh et al, 2022;Iswanto et al, 2021;Jain et al, 2022;Jung et al, 2019Jung et al, , 2021Jung et al, , 2022Manurung et al, 2019;Maulana et al, 2021;Maulina et al, 2020;Min et al, 2019;Purnawati et al, 2018;Seo et al, 2020 Extractives ASTM E 1690…”
Section: Mechanical Propertiesunclassified
“…Compared with planing and sawing, water jet cutting makes smaller kerf widths, fewer dusts, and acceptable noise outputs [66]. Generally, the surface roughness and kerf width are crucial factors determining the quality of wood products [67][68][69].…”
Section: Woodsmentioning
confidence: 99%
“…Lee [69] conducted AWJ cutting on sixteen Korean domestic wood species and found that with the increase in the cutting depth, the surface roughness increased, and the cut width decreased. Gerencsér et al [66] took nine important Hungarian tree species with a thickness of 25 mm as samples to study the influence of AWJ cutting technology on the moisture uptake, surface roughness, and kerf width of solid wood.…”
Section: Woodsmentioning
confidence: 99%